The Shank3-InsG3680(+/+) mouse model of autism spectrum disorder displays auditory avoidance in a novel behavioral test - Gonçalves, Ana Margarida; Sousa, Nuno; Jacinto, Luis; Monteiro, Patricia (Frontiers in Behavioral Neuroscience, 2023)
Autism spectrum disorder (ASD) is characterized by deficits in communication and social interaction, restricted interests, repetitive behaviors, and sensory alterations, being auditory hypersensitivity one of the most commonly reported sensory-perceptual abnormalities. Several candidate genes have emerged from patient studies such as SHANK3, a gene that encodes a protein (SHANK3) in the postsynaptic density of excitatory synapses. Previous work has shown that mutant mice carrying a human ASD-mutation in the Shank3 gene (InsG3680), exhibit repetitive behaviors and social interaction deficits, displaying important construct and face validity as an animal model of ASD. To further address whether these mice also present auditory sensoryperceptual alterations, we developed a novel behavioral test where mice can choose between different soundscapes. Our results reveal that, in comparison to wild-type mice, Shank3-mutants display a strong behavioral preference towards silent regions of the arena. These data suggest that Shank3-mutant mice might have an auditory hypersensitivity phenotype, further adding to its face validity as an animal model of ASD.